The Mediation and Moderation Roles in the influence of Digital Competence and Religious Values on the Sustainability of Sharia Economic Businesses - Puteh, Anwar; Dharma, Yulius; Selian, Rasmila Shundari; Mahera, Ulfa (Journal of Ecohumanism, 2024)
This study aims to investigate the impact of digital competence and religious values on the sustainability of Sharia economic businesses in the digital era. It examines innovation as a mediator and government support as a moderator. Primary data were collected through questionnaires distributed to 200 employees from Sharia banks in Aceh Province-Indonesia. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) in SmartPLS software was employed for data analysis. The findings indicate that both digital competence and religious values positively influence innovation and the sustainability of Sharia economic businesses. Innovation and government support play crucial roles in enhancing the sustainability of these businesses. The indirect effects analysis reveals that digital competence and religious values positively affect the sustainability of Sharia economic businesses through innovation as a mediator. However, the moderating effect of government support on the relationship between innovation and business sustainability shows a small yet significant negative impact. This preliminary study shows promise but highlights the need for more research to understand how digital competence, religious values, innovation, and government support interact to enhance sustainability in Sharia economic businesses. The implications stress integrating digital technology and religious values to promote innovation and sustainable growth in Sharia-compliant enterprises. This pioneering empirical research explores how digital competence and religious values influence the sustainability of Sharia economic businesses in the digital era. It highlights the intricate interplay between innovation and government support crucial for achieving optimal business sustainability outcomes.